Debs : his life, writings and speeches : with a department of appreciations. - Debs, Eugene V. (Eugene Victor), 1855-1926. (Tufts University. Tisch Library., 2016)
1 online resource ([4], ii, [2], 515, [1] pages, [9] leaves of plates) : illustrations, portraits.; Introductory note entitled "The third revolution" (p.[i]-ii) by the compiler and editor, Bruce Rogers.; "Life of Eugene V. Debs, by Stephen Marion Reynolds": p.1-76.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.